Validity evidence of the b ienestar materno en situación de parto scale - Jamas, Milena Temer [UNESP]; de Lucena Ferretti-Rebustini, Renata Eloah; Rebustini, Flávio; Gonçalves, Ivana Regina [UNESP]; Gouveia, Luciana Magnoni Reberte; Hoga, Luiza Akiko Komura (Acta Paulista de Enfermagem, 2021)
Objective: To describe the process of cross-cultural adaptation and validity and reliability evidence of the Brazilian version of the Bienestar Materno en Situación de Parto scale (Maternal Well-being in Childbirth Scale). Methods: This is a methodological study carried out through translation, back-translation, assessment by a committee of judges, pre-test, and validation. Validation included participation of 500 mothers who underwent vaginal childbirth. Exploratory and confi rmatory factor analyzes were performed. Results: After analysis by judges, the suggested changes were applied, and all items showed agreement among evaluators above 80%. Exploratory and confi rmatory factor analysis indicated a satisfactory fi t of the model with three dimensions and good reliability indexes (alpha = 0.95 and omega = 0.94). Conclusion: The short Brazilian version of the Bienestar Materno en Situación de Parto scale is a 16-item scale that presents good validity and reliability evidence.
Keywords: Labor; Maternal welfare; Natural childbirth; Obstetric; Obstetric nursing; Validation studies